Avaliação de uma técnica de diluição e transporte de sêmen eqüino, para as condições Brasileiras - Da Silva Filho, José Monteiro; Fonseca, Francisco Aloízio; Palhares, Maristela Silvelra; Wanderley, Adriana Taveiros; Oliveira, Henrique Nunes [UNESP] (My University, 1998)
Ninety-seven Mangalarga Marchador mares were allocated in a randomized experimental design, with different number of replicates per treatments. The objective of this experiment was to study the effect of raw (T3) or diluted, cooled semen transported to the breeding farms 1 (T1) and 3 (T2), on mare fertility and different aspects of reproductive efficiency. The mares were inseminated, with semen of only one stallion (Farm 2), on alternate days using different inseminating volumes, according to number of inseminated mares per day using only one ejaculate. For transportation, semen diluted in a lactose-egg yolk modified extender and the MSP-2 container were used. There was no difference among treatments in relation to conception rates of marcs inseminated with raw or diluted, cooled and transported semen. Regardless of the farm, the total fertility obtained with cooled semen was 80% (52/65). The following variables were not affected by the treatments: cycles/mare, cycles/pregnant mare, cycles/pregnancy, pregnancy/cycle, number of inseminations/mare, number of inseminations/pregnant mare, number of inseminations/open mare and efficiency of pregnancy. However, the breeding farm had an effect on water and semen temperature in the container, time between collection and insemination, according to time and distance covered. Based on the results, cooling and transporting equine semen, using an extender, lactose-egg yolk without glycerine and the MSP-2 container should be recommended for short distances. The use of raw semen immediately after collection is also recommended.
Evaluation of an equine semen dilution and transport technique to Brazilian conditions
Keywords: Artificial insemination; Cooled semen; Equine; Transported semen